Economic Feasibility Study of Rooftop Solar Power Plant 32 kWp in PT KPJB Office Building, PLTU Tanjung Jati B, Kabupaten Jepara - Sensa Ritzky Cinicy, Oky; Windarta, Jaka; Saptadi, Singgih (Program Studi Magister Energi, Sekolah Pascasarjana, Universitas Diponegoro, Indonesia, 2023)
Strategic initiatives in an effort to increase the role of New and Renewable Energy in the energy mix as a supply of power plants, one of which is the development of Solar Power Plants (PLTS) for own use at PLN's existing Power Plants. In 2021, the percentage of self-use power at PLTU Tanjung Jati B reaches 5.25% or the equivalent of 543 GWh, where PT. KPJB office building is one of the loads that receives self-use from the PLTU grid. Rooftop Solar Power Plant (PLTS) has been implemented on to replace the role of supplying electrical energy from the PLTU to several equipment to support the company's operations. After conducting an economic feasibility study with 3 calculation methods, namely Net Present Value (IDR. 210,436,003.12), Benefit Cost Ratio (1.17), and Payback Period (16.90), theoretically implementing a 32 kWp PLTS Rooftop can indeed said worthy. But with the three calculation results that can be considered very low with an estimated return on investment reaching almost 17 years.